Evaluación del desgaste físico de los cortadores distales de uso ortodóntico mediante microscopia digital. (2023)
In the area of orthodontics, the use of distal cutters in the daily consultation is essential; For orthodontists, cutters represent a considerable economic investment because, depending on the amount of patients treated, a greater number of them would have to be bought.